P76 Long-term effectiveness of a staged assessment for problematic severe asthma. (2nd December 2011) - Sharples, J; Gupta, A; Fleming, L; Bossley, C J; Bracken, M; Hall, P; Hayward, A; Puckey, M; Balfour-Lynn, I M; Rosenthal, M; Bush, A; Saglani, S
Abstract : Background: Children with problematic severe asthma (PA) may have genuine therapy-resistant disease, or may be difficult-to-treat because of unaddressed potentially modifiable factors. Objectives: Evaluate the long-term efficacy of a structured protocol including a nurse-led assessment1 (Stage 1) in identifying modifiable factors and differentiating difficult asthma (DA) from severe therapy-resistant asthma (STRA) in children with PA. As a secondary aim, we determined whether DA and STRA could be identified without the detailed assessment. Methods: 78 children, median age 11.8 years (range 5–17 years), that underwent Stage 1 assessment between 2005 and 2008 were included. Lung function, medications, symptoms and exacerbations were obtained at 1 year, 2 years, and up to 6 years (current status) after initial assessment. Children in whom modifiable factors were identified were classified as DA and those that progressed to further investigations (Stages 2 & 3) as STRA. Results: Median duration of follow-up was 3.9 years (range 2.5–6.1 years). 31/78 (40%) children were classified as DA, and did not proceed to Stages 2 & 3. Children with DA had significantly lower dose inhaled corticosteroids prescribed at follow-up compared to STRA (DA vs STRA: median [IQR] 800 μg [400 μg–1425 μg] vs 1600 μg [800 μg–2400 μg], p<0.05), and significantly fewer oral corticosteroid bursts per year (DA vs STRA: median [IQR] 1 [0–2] vs 4 [1.5–8], p<0.001). DA children had improved lung function at follow-up compared to baseline (median [IQR] FEV1 % predicted: 91% [86.5%–102.5%] vs 80% [73%–86%], p<0.01) despite lower dose inhaled corticosteroids. DA and STRA had different characteristics at baseline: DA children had a higher FEV1 % predicted (p<0.01), less bronchodilator reversibility (p<0.05), lower fractional exhaled nitric oxide (p<0.05), and less sensitisation to food and aeroallergens (both p<0.05) compared to STRA. However, there was considerable overlap between the groups and the two could not reliably be distinguished in advance of the detailed Stage 1 assessment. Conclusion: As a result of our assessment, 40% of children with PA did not undergo invasive investigations and escalation of therapy. Up to 6 years later, children with DA had a significant improvement in lung function and fewer exacerbations despite reduced maintenance medication.